Risk for Infection in Humans after Exposure to Birds Infected with Highly Pathogenic Avian Influenza A(H5N1) Virus, United States, 2022 - Krista Kniss; Kelsey M. Sumner; Katie J. Tastad; Nathaniel M. Lewis; Lauren Jansen; Derek Julian; Mike Reh; Emily Carlson; Robin Williams; Samir Koirala; Bryan Buss; Matthew Donahue; et al. (Emerging Infectious Diseases, 2023)
During February 7─September 3, 2022, a total of 39 US states experienced outbreaks of highly pathogenic avian influenza A(H5N1) virus in birds from commercial poultry farms and backyard flocks. Among persons exposed to infected birds, highly pathogenic avian influenza A(H5) viral RNA was detected in 1 respiratory specimen from 1 person.